Consumption and Preferences for Wild and Domestic Meat in Indigenous Communities in the Brazilian Atlantic Forest - Santos, Claudileide Pereira dos; Braga-Pereira, Franciany; Borges, Anna Karolina Martins; Van Vliet, Nathalie; Alves, Rômulo Romeu Nóbrega (Frontiers in Ecology and Evolution, 2022)
Wild animals have traditionally been the main sources of protein available, if not the only, to numerous indigenous populations worldwide. However, greater access to markets, reduced availability or access to wildlife, and policies in support of agricultural development, have shifted food habits towards domestic and industrial sources of protein. In this study we evaluated consumption patterns and preferences/avoidances for wild animals (wildmeat, crustaceans and fish) in comparison to domestic sources of protein among the Potiguara living on the Brazilian coast. Using data from 843 semi-structured interviews applied to students from 28 indigenous villages, we found that domestic meats were more consumed and preferred as compared to wild animals (aquatic and game animals), despite the abundance of fish and crustacean resources in the surveyed area. Consumption and preference for game was higher among male students while avoidance was higher among female students. Avoidance of domestic meats and fish was low for both genders. The occupation of the fathers affected students’ food habits, in that nature-related occupations (farmer, fisherman/woman, sugarcane worker) conditioned greater consumption of wildmeat and fish, while non nature related occupations lead to greater consumption of protein from domestic sources. The consumption of protein from all sources increased with the distance between villages and a protected area. Our results indicate that the younger generation of Potiguaras does not regularly consume wildmeat and fish and their preference for domestic sources of protein is shaped by the socio-environmental context, access to different types of meat and taste preferences.